FAUNISTIC NOTES ON THE ICHNEUMONIDAE (HYMENOPTERA), WITH A NEW RECORD FROM NORTHEASTERN TURKEY (Acta Entomologica Serbica, 2016)
The present contribution is based upon ichneumonids collected from the northeastern part of Turkey (Bayburt, Erzurum and Kars) in 2007-2009. A total of 7 species belonging to the subfamilies Anomaloninae, Campopleginae, Cremastinae, Cryptinae, Ctenopelmatinae and Tryphoninae have been identified. Among them, Chirotica insignis (Gravenhorst, 1829) is a new record for Turkish fauna. Anomalon cruentatum (Geoffroy, 1785) and Netelia (Netelia) dilatata (Thomson, 1888) are very common in the study area. New data on the distribution of 6 known species are presented. Additionally, a short zoogeographical characterization is given for each of the species.